A thermal degradation (thermolysis) study of rotenone extracted from derris elliptica roots using reverse-phase high performance liquid chromatography (RP-HPLC) - Saiful Irwan Zubairi,; Mohamad Roji Sarmidi,; Ramlan Abdul Aziz, (Universiti Kebangsaan Malaysia, 2015)
Bio-pesticides are becoming increasingly important as pest management tools in various cropping systems in the tropics essentially to remedy problems associated with the indiscriminate use of ‘hard’ and non-environmental friendly inorganic pesticide. In these past few decades, many bio-pesticidal products, both microbial-based (bacteria, fungi, microsprodia, entomopathogenic nematodes and viruses) and plant-based botanicals (rotenone and azadiracthin) have been studied for their use against insect pests in the tropics. In this study, the effects of the concentration process with respect to the yield of rotenone (mg) and its concentration (mg/mL) are presented extensively. The raw plants were collected from Kota Johor Lama, Johor and sorted to obtain the roots and stems. Only the roots and stems were utilized as raw materials of the extraction process. The rotenone from roots and stems was extracted using the normal soaking extraction (NSE) at 28 to 30oC with 95% (v/v) of acetone as a solvent and the solvent-to-solid ratio of 10 mL/g. The extraction was carried out for 24 h. Next, the liquid crude extract was concentrated using the rotary evaporator at 50oC and 80 mbar of vacuum pressure to remove approximately 90% of solvent. The fractions of the liquid crude extract were collected (15 min/mL/fraction), diluted (1/100 with acetone) and cleaned up (to remove any fine debris) prior to determination of rotenone content (mg) and concentration (mg/mL) by using the reverse-phase high performance liquid chromatography (RP-HPLC). Finally, the results showed that there was a significant effect of thermal degradation or dissipation of rotenone content at higher operating temperature (greater than 40oC) with a rapid rotenone reduction for the first 15 min of exposure. The possibilities for better exploitation and identification of the effective operating parameters based on the above mentioned results will be perhaps discussed in the future.